‘Adl as the Pillar of the Caliphate: A Normative Study of Justice in the Concept of Khalifah - Sahibani, Muhammad; Aris Fauzan (Universitas Islam Negeri Raden Intan Lampung, 2025)
Justice (‘adl) is a foundational value in Islamic teachings and constitutes the core pillar of political leadership within the concept of khalifah (caliphate). This article aims to examine the normative meaning, position, and function of justice in the concept of khalifah, based on primary Islamic sources, namely the Qur’an, Hadith, and classical works of fiqh siyāsah. This study employs a qualitative research method with a normative-descriptive approach, utilizing library research as the primary data collection technique. The analysis is conducted through content analysis and thematic interpretation of normative texts and historical practices of Islamic governance. The findings indicate that ‘adl is not merely an ethical value, but a fundamental prerequisite that determines the legitimacy and moral authority of leadership in Islam. Historical evidence from the era of the Khulafā’ al-Rāshidūn demonstrates that justice was systematically implemented in legal administration, public accountability, and equitable distribution of wealth. Classical scholars such as al-Māwardī explicitly emphasized justice as an indispensable requirement for a caliph. Furthermore, this study argues that the normative concept of ‘adl within the caliphate framework remains highly relevant in contemporary Islamic leadership discourse, particularly in promoting accountable, inclusive, and ethically grounded governance. Therefore, justice as the pillar of the caliphate must be continuously recontextualized as a living principle capable of guiding modern political systems in Muslim societies.